THE SHADOW ECONOMY IN THE GLOBAL ECONOMY: PREVENTING LARGE-SCALE CORRUPTION AT THE STATE LEVEL AND DIGITALIZATION OF THE ECONOMY - Xuddiyev Aminjon Alisher o‘g‘li, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the role of the shadow economy in the global economic system, with a particular focus on large-scale corruption at the state level. It analyzes the impact of economic digitalization on reducing informal economic activities and enhancing transparency in public administration. The study highlights the importance of digital tools and e-government systems in preventing corruption and ensuring sustainable economic development.